Identifying Training Needs of Farmers and Rural Youth of Nagaland State - Sajeev, M.V.; Venkatasubramanian, V.; Singha, A.K. (Indian Journal of Extension Education, 2021)
Krishi Vigyan Kendras (KVKs) conduct a variety of trainings for the benefit of farmers and rural youth in each district of the country and it starts with identification of training needs, the most important step in organization of any training programme. The present study on training needs analysis of the farmers and rural youth was conducted by the ICAR-Agricultural Technology Application Research Institute, Umiam in collaboration with the KVKs in Nagaland State. Lists of 11 major components/ thematic areas were prepared. Under each major component, specific and relevant training need items were collected and systematically incorporated in the interview schedule and administered. The results revealed that even in the most popular areas of training, there was an inadequacy. Farmers sought maximum trainings on weed management in field crops followed by training on cropping system and integrated farming system. In area of soil health and fertility management, training on technologies for management of soil fertility followed by soil and water conservation techniques were in much demand. Cultivation of off season vegetables and canopy management topped the list under horticulture while training with respect to rearing of piggery was the most important one under animal sciences. The KVKs have to re-orient their trainings based on these findings to reduce the existing technological and adoption gap among the farmers in Nagaland.
Keywords: Nagaland; Farmers; KVKs; Rural Youth; Training needs